Vicarious dissonance and the narrative of the Gospel of Matthew - Pisilä, Mikko (Approaching Religion, 2018)
This article presents a novel social-scientific approach to the Gospel of Matthew, one of the most influential texts in the history of Christianity. This approach combines social-psychological and narrative-critical methodology. The aim is to demonstrate how the gospel narrative functions to transform the social identity of its audience and stimulate group commitment via the social-psychological phenomenon of vicarious cognitive dissonance.